Kapitalisasi Isu Syariah Terhadap Pergerakan Ekonomi Di Pasar Nasional Dan Global - Wening Purbatin Palupi Soenjoto; Septiyan Hudan Fuadi (JOURNAL OF SHARIA ECONOMICS, 2020)
This study aims to determine the effect of the capitalization of sharia issues on economic movements in national and global markets and try to answer the problem formulation, namely: first, it can describe capitalization of sharia issues that are starting to develop in sharia economic movements in national and global markets. Second: can describe the process of negotiation (interaction) carried out by producers who use sharia issues in trade. Third: can find the implications of the meaning of the results of research and solutions that can add studies related to sharia issues in the economy in national and global markets so that it can be further investigated by subsequent researchers. The method used in this study is a qualitative method with descriptive analysis. Research subjects are informants who provide research data through interviews, surveys and documentation with triangulation data processing techniques to obtain valid research results. Based on the results of the study, it was concluded that the capitalization of sharia issues could affect national and global market movements Keywords: Capitalization, Sharia Issues, Sharia Economy, National Market, Global Market